The Role of Child Psychological Test Results in Custody Decisions in Divorce Cases - Indana Zulfah; Idha Aprilyana Sembiring; Rosmalinda (Universitas Islam Negeri Walisongo Semarang, 2025)
This study examines the urgency of documentary evidence in the form of child psychology test results as a consideration for judges in determining child custody (hadanah) in divorce cases. Legal decisions in divorce cases in Medan (2021) prioritize the best interests of children, especially those who are still minors and vulnerable to psychological trauma due to conflict and parental separation. The results of child psychology tests serve as formal indicators of trauma or emotional disturbance and can help identify which parents provide a safer and more emotionally stable environment. This article uses a normative legal research method with a statutory and conceptual approach and is supported by a comparative study of first-instance court decisions. Empirical data obtained from interviews with psychologists and several judges at the Medan Religious Court show that child psychological assessments are often submitted but rarely considered by judges in their final decisions. This study criticizes the court's decision to grant custody to parents who have a history of violent behavior based on the results of psychological tests, which causes the child to show fear and be reluctant to interact with his mother. This article concludes that the principle of justice for children as the primary victims should be reviewed and emphasized and that psychological test results should be considered as crucial legal evidence in child custody decisions. Artikel ini mengkaji urgensi alat bukti surat berupa hasil analisis tes psikologi anak sebagai bahan pertimbangan hakim dalam menetapkan hak asuh anak (hadanah) dalam perkara perceraian. Putusan hukum dalam perkara perceraian di Medan (2021) mengutamakan kepentingan terbaik anak, terutama yang masih di bawah umur dan rentan mengalami trauma psikologis akibat konflik dan perpisahan orang tua. Hasil tes psikologi anak berfungsi sebagai indikator formal adanya trauma atau gangguan emosional, serta dapat membantu mengidentifikasi orang tua mana yang memberikan lingkungan yang lebih aman dan lebih stabil secara emosional. Artikel ini menggunakan metode penelitian yuridis normatif dengan pendekatan perundang-undangan dan konseptual serta didukung oleh studi banding putusan pengadilan tingkat pertama. Data empiris yang diperoleh dari wawancara dengan psikolog dan beberapa hakim di Pengadilan Agama Medan menunjukkan bahwa penilaian psikologis anak sering diajukan tetapi jarang dipertimbangkan oleh hakim dalam keputusan akhir mereka. Penelitian ini mengkritik keputusan pengadilan yang memberikan hak asuh kepada orang tua yang memiliki riwayat perilaku kekerasan berdasarkan hasil tes psikologis, yang menyebabkan anak tersebut menunjukkan rasa takut dan enggan berinteraksi dengan ibunya. Artikel ini menyimpulkan bahwa prinsip keadilan bagi anak sebagai korban utama harus ditinjau kembali dan ditekankan, dan bahwa hasil tes psikologi harus dipertimbangkan sebagai bukti hukum yang penting dalam putusan hak asuh anak. Keywords: Child; Psychological Test; Hadanah; Divorce Cases.